The only way for minority cultural survival. (March 2018) - Bell, Adrian
Asymmetric social boundaries allow a minority culture to reap the benefits of outside interaction while maintaining its distinctiveness. This opens questions about the nature of intergroup interactions and whether such boundaries are the only way to preserve valued cultural norms.